The New Predator : Profiles Of Female Serial Killers. - Schurman-Kauflin, Deborah (Algora Pub., 2007)
This is the first book ever written on the basis of face-to-face interviews with women serial killers. The author, a professional criminal profiler, analyzes the common features and the distinctions between women and men who kill, and their crimes and cri.